Irisin: A Hope in Understanding and Managing Obesity and Metabolic Syndrome - Arhire, Lidia I.; Mihalache, Laura; Covasa, Mihai (Frontiers in Endocrinology, 2019)
White adipose tissue (WAT) is an endocrine organ highly integrated in homeostasis and capable of establishing ways of communicating and influencing multiple metabolic processes. Brown adipose tissue [1] promotes energy expenditure by incorporating in the mitochondrial membranes the uncoupling protein 1 (UCP1) also known as thermogenin, that decouples cellular respiration and heat production. Recent data suggest the presence of a thermogenic cell formation from white adipocytes (beige or brite cells) with a potential role in preventing obesity and metabolic syndrome. Formation of these cells is influenced by physical exertion that induces expression of PPARγ coactivator-1 (PGC1) and downstream membrane protein, fibronectin type III domain-containing protein 5 (FNDC5) in skeletal muscle. Irisin, a thermogenic adipomyokine produced by FNDC5 cleavage is involved in browning of adipose tissue. While animal studies are congruent with regard to the relationship between physical exertion and irisin release, the results from human studies are less than clear. Therefore, this review focuses on recent advances in our understanding of muscle and adipose tissue thermogenesis. Further, it describes the molecular mechanisms by which irisin impacts exercise, glucose homeostasis and obesity. Finally, the review discusses current gaps and controversies related to irisin release, its mode of action and its future potential as a therapeutic tool in managing obesity and metabolic syndrome.